ナンキョク プレート ノ コウゾウ ト シンカ ニ カンスル コクサイ ワークショップ (SEAP2003) ホウコク - 金尾, 政紀; カナオ, マサキ; 澁谷, 和雄; シブヤ, カズオ; 小林, 励司; コバヤシ, レンジ; Kanao, Masaki; Shibuya, Kazuo; Kobayashi, Reiji (2004)
P(論文) 平成15年3月3日3月5日にボルダー(アメリカ)において開催された「南極プレートの構造と進化に関する国際ワークショップ」(Structure and Evolution of the Antarctic Plate 2003; SEAP2003)に参加した.南極大陸を中心とした南極プレート内部の構造と進化過程に関する地震学的研究を進めていく上で,国際協力を踏まえた今後10年間の重点的な研究テーマや観測手法について様々な討論を行った.アメリカを中心にヨーロッパやオセアニア,アジア等,計9カ国から計97名の参加があった.南極内陸部での科学的研究の柱として,可般型広帯域地震計によるアレイ観測(Antarctic Array)が挙げられた.Antarctic Arrayは,1)大陸全体規模での定常観測ネットワーク(Continental Network)の構築,2)地域的規模での「刈り取り的」アレイ観測(Regional Leapfrogging Arrays),3)目的を絞った3次元的アレイ観測(3-D Array)から構成される.現在,宗谷海岸を中心に行っている広帯域地震計アレイをはじめとして,今後も国際状況の経過を見守りつつ積極的に観測協力に取り組みたいと考える. A workshop on "Structure and Evolution of the Antarctic Plate 2003 (SEAP2003)" was held on March 03-05, 2003 at Boulder, Colorado, USA, with 97 participants. The purpose of this workshop was to develop a long-term science plan to improve understanding of the structure and evolution of the Antarctic Plate. In particular, the scientific justification and feasibility of the program to improve seismic instrumentation on and around the Antarctic continent was a centerpiece of the workshop. It is important to consider the context for the development of the Antarctic Array both with respect to international cooperation and for coordination with other scientific initiatives both within and marginal to Antarctica. Portable broadband seismic array deployments along the coastal area around Syowa Station by the Japanese Antarctic Research Expedition (JARE) will contribute to the above international Antarctic Array. departmental bulletin paper